Evaluation of Information Quality Kupang City Government Website - Aryanthy Sintikhe Elizadon Puling; Melkior Nikolar Ngalumsine Sitokdana (Politeknik Pertanian Negeri Samarinda, 2020)
Kupang Municipal Government long enough to have a website with a domain name v8.kupangkota.go.id. In this research will be used a descriptive qualitative method, which describes and illustrate the content Government website that have been set by the Ministry of Communications and the use of 10 (ten) dimension of the quality of information that is Accuracy, Consistency, Punctuality, Completeness, Reliability, Availability, Relevancy, Credibility, Efficiency and Value-Added. Based on the results of the evaluation of the quality of Kupang City Government Website information, it can be concluded that the website was not fully present enough quality information for the public. There are still some shortcomings such as the lack of an increase in accuracy of presentation of information, the lack of consistency in the presentation of information as there are pages in which there are three (3) categories that are not accessible or not there is any information. The website is expected to not only serve as a source of information that is passive but dynamic so that the function and role of the website reciprocal effect. In addition, the provincial government should continue to ensure data is always updated and complete, permanent increase in the added value of public services and still make the website as the main medium of public information services.